EFEK PEMBERIAN KAPSUL EKSTRAK JAMU HIPERGLIKEMI TERHADAP KUALITAS HIDUP: The Effect of Hyperglycemic Herbal Extract Capsules on Quality of Life - Ulfa Fitriani; Agus Triyono; Danang Ardiyanto; Zuraida Zulkarnain; Peristiwan Ridha Widhi Astana; Ulfatun Nisa; Fajar Novianto; Enggar Wijayanti (Jurnal Tumbuhan Obat Indonesia, 2023)
Quality of Life (QoL) in diabetes mellitus (DM) has become highly emphasized in recent years as health care outcome. Hyperglicemic herbs potio, one of scientific herbs, has been proven to be safe and efficacious. The use of extract capsules as an innovative form of herbal medicine continues to be developed. The study aimed to examine the effect of giving hyperglicemic herbal extract capsules on the QoL of hyperglycemic patients at Rumah Riset Jamu (RRJ) Hortus Medicus. The method used was pre and post-test design with quasi-experimental. A total of 60 patients followed the study during September-November 2019. The hyperglycemic herbs formula consisting of 5 grams daun Salam, 5 grams sambiloto, 7 grams kayu manis and 10 grams temulawak which converted to the one extract capsule. For the daily doses are two capsules twice a day. The Metformin 500 mg single dose as a control of the study. Before this study and on day 28th, the patients had been examined the QoL using the short form-36 (SF-36). The data were analyzed using the Wilcoxon and Mann Whitney test. The results showed that there was a significant increase in total score of SF-36 (p=0,000) between before and after taking extract capsules, especially for the general health domain (p=0,002). The total score of SF-36 between extract capsules and Metformin groups was not significantly difference (p=0,323). Hyperglycemic herbal extract capsules improved the QoL of the hyperglycemic patients.